Revised, Complementary techniques for pigment analysis from the festival hall of Thutmosis III, the Karnak temples complex (Luxor, Egypt) - Marey Mahmoud, Hussein Hassan (Archeomatica, 2013)
The present paper aims at analyzing some ancient pigments from the festival hall of Thutmosis III, the Karnak temples complex (Luxor, Egypt). The wall decorations of the festival hall are carved with raised and sunken reliefs and painted with religious scenes and hieroglyphs texts. The analytical techniques utilized in this study were optical microscopy (OM), environmental scanning electron microscopy (ESEM) coupled with an energy dispersive X-ray analysis system (EDX), Î¼-X-ray fluorescence spectrometry and colorimetry. Based on the results of these analyses, the microscopic features, microstructure and the chemical composition of the studied pigments were identified. The results revealed the blue pigment as Egyptian blue (cuprorivaite, CaCuSi4O10), the green pigment as Egyptian green (Cu-wollastonite), the yellow pigment as yellow ochre, and the red pigment as red ochre.